Geometric optimization associated with the use of high-strength concrete in viaducts - TRENTINI,E. V. W. (2019)
Abstract In Brazil, there is a lack of infrastructure investment in roads, given that they facilitate the transportation of more than half the country’s cargo volume. One of the main variables in road infrastructure is overpass construction and maintenance. Concrete overpasses with post-tensioned I-section beams have been extensively used in Brazil. This study discusses the economic aspects of the use of high-strength concrete (HSC) associated with the geometrical optimization of decks of post-tensioned multi-girder overpasses. Twelve overpass decks were dimensioned and divided into two groups. In Group A the characteristic concrete strength varied, but not the geometrical characteristics of the deck. In Group B, the characteristic strength and the geometrical characteristics of the deck varied. These were the configurations that presented the best results for each group of characteristic concrete strength. It was determined that the use of HSC significantly decreases the reinforcement ratio-especially shear reinforcement. In addition, although the HSC has a higher cost per m3, it is still considered a viable option owing to the reduction in the reinforcement ratio. Lastly, in addition to providing the benefits that are widely commented on in literature, using HSC can also provide more economical overpass structures compared to conventional concrete.